STRATEGI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU YANG TELAH LULUS JLPT N3 - Nurul Fadhilah; Hadriana Hadriana; Merri Silvia Basri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Japanese Languange Proficiency Test (JLPT) is a test held to measure Japanese language skills. This study aims to find out how the use of learning strategies according to Oxford (1990) by students who have passed JLPT N3. This study used descriptive qualitative method. The study was conducted by conducting interviews with data sources. The data sources in this study were 7 students of class 2017 and 1 student of class 2018 Japanese language education study program Riau University. The results of this study indicate that students who have passed JLPT N3 use learning strategies according to Oxford (1990) in various ways in each strategyKey Words: JLPT, Learning Strategies, Oxford.